2020
DOI: 10.3390/su12229451
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Soil Water Content and Evapotranspiration of Winter Wheat under Deficit Irrigation Based on SWAP Model

Abstract: Deficit irrigation strategy is essential for sustainable agricultural development in arid regions. A two−year deficit irrigation field experiment was conducted to study the water dynamics of winter wheat under deficit irrigation in Guanzhong Plain in Northwest China. Three irrigation levels were implemented during four growth stages of winter wheat: 100%, 80% and 60% of actual evapotranspiration (ET) measured by the lysimeter with sufficient irrigation treatment (CK). The agro−hydrological model soil−water−atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…Several studies [10,11] assumed a fixed value of the seasonal evaporation loss (110 mm) when determining water availability for rainfed wheat, which seems unreasonable. However, inter-and intra-season variabilities in the evaporation losses are common and are highly correlated with the diurnal and seasonal changes in the climate parameters and ground cover [61]. In the current study, seasonal E s losses were 5-30% lower than a fixed value (110 mm) suggested by French and Schultz [10].…”
Section: Soil Water Balance and Wheat Water Uptakecontrasting
confidence: 60%
See 2 more Smart Citations
“…Several studies [10,11] assumed a fixed value of the seasonal evaporation loss (110 mm) when determining water availability for rainfed wheat, which seems unreasonable. However, inter-and intra-season variabilities in the evaporation losses are common and are highly correlated with the diurnal and seasonal changes in the climate parameters and ground cover [61]. In the current study, seasonal E s losses were 5-30% lower than a fixed value (110 mm) suggested by French and Schultz [10].…”
Section: Soil Water Balance and Wheat Water Uptakecontrasting
confidence: 60%
“…During the validation period (2019), the error values varied from −0.04 to 0.07 cm 3 cm −3 . Wang et al [61] reported RMSE and mean relative error (MRE) values of 0.07 cm 3 cm −3 and 21.6%, respectively, as accurate estimation of water content dynamics in the soil by SWAP model under wheat irrigated with varied levels of deficit irrigations. Error estimates reported in other studies [37,62] also corroborate well with the values estimated in the current study, which showed a good agreement between measured and simulated water content dynamics in the soil.…”
Section: Soil Water Dynamics In the Soilmentioning
confidence: 99%
See 1 more Smart Citation